Two novel genera and one new species of treefrog (Anura: Rhacophoridae) highlight cryptic diversity in the Western Ghats of India - Abraham, Robin Kurian; Pyron, R. Alexander; R., Ansil B.; Zachariah, Arun; Zachariah, Anil (Zootaxa, 2013)
Amphibian diversity in the Western Ghats-Sri Lanka biodiversity hotspot is extremely high, especially for such a geo-graphically restricted area. Frogs in particular dominate these assemblages, and the family Rhacophoridae is chief among these, with hundreds of endemic species. These taxa continue to be described at a rapid pace, and several groups have recently been found to represent unique evolutionary clades at the genus level. Here, we report DNA sequences, larval and breeding data for two species of rhacophorid treefrog (Polypedates bijui and a new, hitherto undescribed species). Re-markably, they represent unique, independent clades which form successive sister groups to the Pseudophilautus (Sri Lan-ka) + Raorchestes (India, China & Indochina) clades. We place these species into two new genera (Beddomixalus gen. nov. and Mercurana gen. nov.). Both of these genera exhibit a distinct reproductive mode among Rhacophoridae of pen-insular India and Sri Lanka, with explosive breeding and semiterrestrial, unprotected, non-pigmented eggs oviposited in seasonal swamp pools, which hatch into exotrophic, free-living aquatic tadpoles. Relationships and representation of re-productive modes in sister taxa within the larger clade into which these novel genera are placed, is also discussed. These results suggest that more undescribed taxa may remain to be discovered in South Asia, and the crucial importance of con-serving remaining viable habitats.